Network analysis and agent-based modeling of micro-businesses - Andino-González, Patricia; Acosta-Tzin, Jose Valdo; Raudales-García, Elí Vicente; Aguilar-Hernández, Pablo Alcides; Andino-González, Patricia; Acosta-Tzin, Jose Valdo; Raudales-García, Elí Vicente; Aguilar-Hernández, Pablo Alcides (Corporación Universitaria Americana, 2024)
Introduction: The analysis of the structures of social networks and agent-based simulation models allow to know and analyze the behavior of the different actors interacting within a system. Objective: To conduct a network analysis and agentbased modeling of microbusinesses to understand, identify and compare the existing relationships and behavior among actors, suppliers, creditors, public and private institutions ofmicrobusinesses in the grocery industry in the central district of Honduras through a simulation model. Methodology: This local study was carried out with a descriptive nature, under a mixed approach where data were collected through interviews with managers of the The data were collected through interviews with managers of micro-businesses that represent the entirepopulation of the study unit. Results: Pajek software was used for the elaboration of the network systems and NetLogo was used for the development of the simulation model. Conclusions: The centrality and density of the actors in a network, together with the modeling through simulation, allows us to know theapproximations and behavior of the agents that approaches and behavior of the agents that guarantee the sustainability and productivity of micro-businesses.